Blockchain for medical research : accelerating trust in healthcare / Sean T Manion; Yaël Bizouati-Kennedy - Manion, Sean T.
It takes 17 years on average to bring new health ideas into evidence-based clinical practice. The growing replicability crisis in science further delays these "new miracles." Blockchain can improve replicability and hasten the knowledge translation process. This book is about science, its value to our health, and how we can use blockchain to improve its quality and impact. The book will look at science and medicine from an insider's perspective, and describe the processes, successes, shortcomings and opportunities for advancement for the lay audience. It will give the reader a non-technical look at the emerging world of blockchain technology; what it is, where it is useful, and how it can improve science and health. It will lay out a roadmap for this application to transform how we develop knowledge about disease and accelerate cures to improve our lives. In the first part, the authors look at science as a process and how this drives advancement in medicine. They'll then shed a light on some of science's shortcomings, including the reproducibility crisis and problems with misaligned incentives (i.e. publish or perish). The book applies a breakdown of critical components to the functional steps in the scientific process and outlines how the open science movement is looking to improve these. It will also highlight the limit of these fixes with current technology, incentives and structure of science. The second part, looks at the history of distributed ledgers from pre-computer versions to the current applications of blockchain/distributed ledger technology and gives an overview of use cases for the technology across industries, including finance, manufacturing and healthcare. Additional focus will be provided to the application challenges with more complex data systems and the need for a contributing network of users. The third and last part, looks at the principle of a distributed autonomous organization (DAO) applied to the health sciences. The authors examine how this distributed approach can provide better quality science, value-based research and faster medical miracles. Finally, the authors will provide a vision of the future of distributed health science in the structure of a DAO and give a roadmap of steps to get there